Real-time Environment for the Design and Evaluation of Fuzzy Controllers - Cofman, Fernando (2003)
This paper presents the results of the implementation of Fuzzy PID control strategies on a complex, critically-stable system, namely the PID-Pong machine. Two different fuzzy algorithms are implemented in real-time and compared to a linear PID controller, used as the evaluation basis. Conclusions are established based on regulation, implementation and tuning indicators